Analysis of Lexical Retrieval Strategies During Tip-of-the-Tongue (TOT) States among English Education Students - Rajagukguk, Sahmiral Amri; Siregar, Amanda; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study investigates how English Education students experience and resolve Tip-of-the-Tongue (TOT) states during English word retrieval. The research uses a qualitative descriptive design to explore students’ natural responses and strategies when they temporarily cannot recall a word. Fifteen seventh-semester students from an English Education Department in Medan participated in individual observation sessions. The data were collected using a PowerPoint presentation containing twenty visual stimuli designed to trigger TOT moments and were analyzed through transcription, coding, and triangulation. The findings show that proper nouns were the most common triggers of TOT states, followed by uncommon concrete and abstract nouns. Five main types of retrieval strategies were identified, including phonological, semantic, gestural, interlingual, and associative strategies. Among them, phonological strategies were most frequently used, followed by semantic strategies, suggesting that learners rely heavily on sound and meaning cues to retrieve words. These results highlight how English learners manage lexical difficulties and show that TOT experiences can provide useful insight into mental lexicon functioning. The study also implies that raising awareness of retrieval strategies may help teachers design speaking and vocabulary activities that support faster word recall and reduce hesitation in communication.